Governance And Mass Migration Of Nigerians Abroad: The Causes And Consequences - Adegbami, Adeleke; Osungboye, Biola Muhibat (Universitas Airlangga, 2024)
Abstract The optimism that civilian administration in Nigeria's Fourth Republic would catalyze unparalleled development has gradually waned as Nigerians continue to grapple with precarious economic conditions. A significant proportion of the country’s annual revenue is allocated to servicing domestic and external debts, further diminishing prospects for an improved quality of life. Within this context, this study explores the driving factors behind the mass migration of Nigerians, the preferred destinations of these migrants, and the broader implications of this migration on Nigeria and its citizens. Utilizing both primary and secondary data sources—including direct observations, textbooks, academic journals, official records, and resources from Nigerian government and international organization websites—the study identifies several interrelated drivers of migration. These include widespread poverty, high unemployment rates, poor economic conditions, an underfunded public healthcare system, escalating insecurity, and persistent political challenges. Popular destinations for Nigerian migrants include the United States, the United Kingdom, Italy, Germany, France, and Canada. The findings reveal both positive and negative impacts of mass migration. On one hand, remittances from migrants provide a critical source of income and contribute to economic development. On the other hand, significant challenges arise in key sectors, particularly healthcare and education. For instance, migration-induced shortages of healthcare professionals compromise service delivery, while the outflow of university lecturers creates gaps in research and teaching capacities. Additionally, funds spent by students on tuition fees abroad could otherwise be invested in strengthening Nigeria’s domestic education system. The study concludes that curbing mass migration requires substantive improvements in governance, including the creation of employment opportunities, poverty alleviation, enhanced security, access to quality education and healthcare, improved labor conditions, and an overall elevation in living standards. Keywords: Governance, Mass migration, Poverty, Unemployment, Insecurity, Violent conflict Abstrak Optimisme pemerintahan sipil di Republik Keempat Nigeria akan mendorong perkembangan yang tak tertandingi secara perlahan memudar karena rakyat Nigeria terus menghadapi kondisi ekonomi yang genting. Sebagian besar pendapatan tahunan negara dialokasikan untuk membayar utang dalam negeri dan luar negeri, sehingga semakin memperkecil peluang masyarakat untuk menikmati peningkatan kualitas hidup. Dalam konteks ini, studi ini mengeksplorasi faktor-faktor yang mendorong migrasi massal warga Nigeria, destinasi utama para migran, serta dampak lebih luas dari migrasi ini terhadap Nigeria dan warganya. Dengan menggunakan sumber data primer dan sekunder termasuk observasi langsung, buku teks, jurnal akademik, catatan resmi, serta sumber daya dari situs web pemerintah Nigeria dan organisasi internasional, studi ini mengidentifikasi sejumlah faktor saling terkait yang mendorong migrasi. Faktor-faktor tersebut mencakup kemiskinan yang meluas, tingginya tingkat pengangguran, kondisi ekonomi yang buruk, sistem kesehatan publik yang kurang terdanai, meningkatnya ketidakamanan, serta tantangan politik yang terus berlanjut. Destinasi utama bagi para migran Nigeria meliputi Amerika Serikat, Inggris, Italia, Jerman, Prancis, dan Kanada. Temuan studi ini mengungkapkan dampak positif dan negatif dari migrasi massal. Di satu sisi, remitansi dari para migran menjadi sumber pendapatan penting dan berkontribusi pada pembangunan ekonomi. Di sisi lain, tantangan signifikan muncul di sektor-sektor utama, khususnya kesehatan dan pendidikan. Misalnya, kekurangan tenaga kesehatan akibat migrasi mengurangi kualitas layanan kesehatan, sementara migrasi dosen universitas menciptakan kekosongan dalam kapasitas penelitian dan pengajaran. Selain itu, dana yang dihabiskan mahasiswa untuk biaya pendidikan di luar negeri seharusnya dapat diinvestasikan untuk memperkuat sistem pendidikan domestik Nigeria. Studi ini menyimpulkan bahwa mengurangi migrasi massal membutuhkan perbaikan signifikan dalam tata kelola, termasuk penciptaan lapangan kerja, pengentasan kemiskinan, peningkatan keamanan, akses terhadap pendidikan dan layanan kesehatan berkualitas, perbaikan kondisi tenaga kerja, serta peningkatan standar hidup secara keseluruhan. Kata kunci: Tata kelola, Migrasi massal, Kemiskinan, Pengangguran, Ketidakamanan, Konflik kekerasan.